Trends in educational disparities in preventive behaviours, risk perception, perceived effectiveness and trust in the first year of the COVID-19 pandemic in Germany - Timo-Kolja Pförtner; Simone Dohle; Kira Isabel Hower (BMC Public Health, 2022)
Abstract Background Educational disparities in health and health behaviours have always been relevant in public health research and are particularly challenging in the context of the COVID-19 pandemic. First studies suggest that factors important for the containment of the COVID-19 pandemic, such as prevention behaviour, risk perception, perceived effectiveness of containment measures, and trust in authorities handling the pandemic, vary by educational status. This study builds on recent debate by examining trends in absolute and relative educational disparities in these factors in the first year of the COVID-19 pandemic in Germany. Methods Data stem from four waves of the GESIS Panel surveyed between March and October 2020 in Germany (15,902 observations from 4,690 individuals). Trends in absolute and relative disparities were examined for preventive behaviour, risk perception, perceived effectiveness of COVID-19 containment measures, and trust in individuals and institutions handling the COVID-19 pandemic by educational status using sex, age, residence, nationality, children under 16 living in household, family status, household size, the Big Five Inventory, and income class as control factors. Descriptive statistics as well as unadjusted and adjusted linear regression models and random effects models were performed. Results We observed an initially rising and then falling trend in preventive behaviour with consistent and significant absolute and relative disparities with a lower preventive behaviour among low educated individuals. Indication of a U-shaped trend with consistent significantly lower values among lower educated individuals was found for risk perception, whereas perceived effectiveness and trust decreased significantly over time but did not significantly vary by educational status. Conclusions Results indicate persistent educational disparities in preventive behaviour and risk perception and a general decline in perceived effectiveness and trust in the first year of the COVID-19 pandemic in Germany. To address this overall downward trend and existing disparities, comprehensive and strategic management is needed to communicate the risks of the pandemic and the benefits of COVID-19 containment measures. Both must be adapted to the different needs of educational groups in particular in order to overcome gaps in preventive behaviour and risk perception by educational status.